Modeling of long-term radiological and toxicological impacts of the uranium mill tailings on groundwater and surface water - B. Yu. Zanoz; D. O. Bugai (Ядерна фізика та енергетика)
Modeling predictions are presented of radionuclide transport processes in the zone of influence of the Zahidne uranium mill tailings situated at the Prydniprovsky Chemical Plant (PChP), Kamianske. The groundwater transport model was developed using the NORMALYSA software. Refined estimates of parameters of water exchange in the zone of uranium mill tailing (obtained from field studies and modeling of groundwater flow processes) were used to parameterize the model for radionuclide transport in groundwater. Calibration of the radionuclide transport model using monitoring data on radioactive contamination of groundwater in 2005 - 2021 allowed to estimate the sorption distribution coefficient (Kd) for the most hazardous contaminants 238,234U isotopes (Kd = 8 ± 2 l/kg) and estimate the rate of uranium migration in groundwater. According to modeling, during the next 800 to 1100 years, uranium concentration in wells in the zone of influence of uranium mill tailing (at 500 - 800 m distance) will be determined mainly by the contamination of the alluvial aquifer, which was formed during the operation period of the uranium mill tailing. According to modeling predictions, usage of groundwater (partial drinking water consumption, irrigation) outside the PChP site downstream of the uranium mill tailing will result in doses exceeding the relevant reference level (annual effective dose > 1 mSv/year) in 380 - 440 years, while the toxicological impact will result in the exceeding of the acceptable hazard index for uranium (HI > 1) in 200 - 260 years. Modeling results indicate the importance of restricting the use of groundwater downstream of the uranium mill tailing within the PChP industrial site and, in the longer term, beyond its boundary. At the same time, contamination of the Konoplyanka River due to the migration of radionuclides from the uranium mill tailing does not pose unacceptable radiological and toxicological risks for the considered scenario (irrigation, fish consumption) due to the dilution of contaminants in surface waters.